Structure-function studies of the bacterial dsDNA translocase FtsK - Graham, JE (2010)
DNA translocases are molecular motors that use energy from nucleotide triphosphate (NTP) hydrolysis to move along, pump, remodel or clear DNA. Unlike helicases, double-stranded DNA (dsDNA) translocases do not unwind DNA; their action has no net product apart from inducing supercoils as a result of groove-tracking, which has hampered their characterisation. Many dsDNA translocases appear to have biased directionality. However, the inherent symmetry of dsDNA requires that translocase activity is regulated by specific sequences or through modulation by interaction partners. FtsK is a highly conserved bacterial cell-division protein, localised to the dividing septum, that coordinates chromosome segregation with cytokinesis. It is responsible for the resolution of chromosome dimers by activating the tyrosine recombinases XerCD bound to the 28bp chromosomal site dif. The C-terminal domain of FtsK (FtsKC) is a dsDNA translocase (speed ~5 kb/s, stall force ~60 pN) most closely related to superfamily 4 helicases and is active as a hexameric ring. A winged-helix subdomain at the C-terminus of FtsKC, FtsKgamma, binds to specific 8 bp sequences, KOPS, that are polarised in the bacterial chromosome from the origin to towards dif. FtsKgamma also interacts with XerD, activating it for catalysis. Studies of FtsK translocation have differed over whether KOPS act as a loading or a reversal sequence for FtsK. In Chapter 2, I use a continuous ensemble assay for dsDNA translocation to show that FtsK initiates rapidly at KOPS, with loading dependent on FtsKgamma. Translocation requires moderately cooperative ATP binding, while ATP hydrolysis has a more relaxed cooperativity. I have determined the ATP coupling efficiency of translocation to be ~1.6 bp/ATP, in line with theoretical estimates. Though FtsK probably strips most proteins from DNA, I show in Chapter 3 that FtsK stops translocating when it encounters XerCD bound to dif. The interaction is most likely a specific down-regulation, but surprisingly does not depend on FtsKgamma or on the catalytic or synaptic activity of XerCD. In Chapter 4, I show some preliminary structural data of FtsKC bound to dsDNA, with the aim of determining the first high resolution structure of a ring dsDNA translocase bound to nucleic acid.